Map in the Mystery Machine - Herman, Gail, 1959-; Duendes Del Sur (Firm) (New York : Scholastic, 2000)
Scooby and the gang find an old map that leads them on a wild adventure.
At head of title: Cartoon Network.
"WB Worldwide Publishing."
150
Accelerated Reader AR
Keywords: Lost and found possessions -- Fiction; Mystery and detective stories